PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA ANGGOTA DENMA SESKOAL (Detasemen Markas Sekolah Staf dan Komando Angkatan Laut) - Sulastri Sulastri; Suharto Suharto; Iwan Kurniawan Subagja (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Human resources (HR) is one component that exists in organizations other than machine, money, materials, methods, and markets. An agency must be supported by competent human resources because human resources play an important role in running a business or activity within the agency. Seskoal is the highest general development education in the Indonesian Navy and has the main task in deepening the material of the struggle and the study of defense issues at the sea level of strategy and operations within the Navy. In Seskoal this is where the Student Officers are forged to become strategic level sea defense scholars. In carrying out this task, Denma Seskoal members are required to have high performance in order to produce good quality work. The factor of Human Resources (HR) is a determinant of the level of ability of Members of Denma Seskoal. As the main factor, members must have high quality, discipline and high work motivation. The type of research used in the study is quantitative, the data source used is the distribution of questionnaires given to members of Denma Seskoal. While the data analysis method used in this study used SPSS 2.0. Correlation coefficient (R) shows how closely the relationship between Discipline independent variables (X1) with non-independent variable Member Performance (Y), the value of the correlation coefficient is 0.637. This value indicates that the relationship of the Discipline variable (X1) with the Member Performance variable (Y) is 63.7%. While Work Work Motivation (X2) with non-independent variable Member Performance (Y), the value of the correlation coefficient is 0.674. This value shows that the relationship of the Work Motivation variable (X2) with the Member Performance variable (Y) is strong, which is 67.4%. Based on the calculation of the partial correlation, Motivation of work which gives the biggest contribution.